(3GdMeGjI GdbGfhfjI ddcajd (B: s (3OQGSI ebGQfI (B/ s - (3GMeO QeVGf eMehO eMeO,s; (3YHOGdgGOi ahRi GdYhVis; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI(B:s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2022)
(3JYJHQ GdcaGdI ai GdhbJ GdMGVQ, ef Hjf CcKQ GdYbhO QhGLG ai GdeLJeYGJ GdeJMVQI, hjQLY Pdc Edi GdJWhQ GdSQjY GdPj jTgOg gPG GdYUQ ai GdeYGedGJ GdeOfjI hGdJLGQjI hGJSGY fWGb GSJYeGdgG djS HGdWQb GdJbdjOjI aMSH, Hd hHGJ ef GdeSJMjd GdMUhd Ydi GdGFJeGf , eG de jcf gfGc VGef jJYgO HGdhaGA HGdOjf GdeVehf hPdc YfOeG dG jbhe GdeOjf HGdhaGA GdahQj YfO Mdhd CLdg hEdG hbYJ GdeSFhdjI Ydi gPG GdVGef GdPi JYgO HGdVeGf HGdOjf Gdecahd(B. (3hdeG cGfJ GdcaGdI JbOe NOeI LdjdI dCaQGO GdeLJeY, agfGc GdJRGe hGMO SjfTC Ydi TNU hGMO jSei Gdcajd, hjJMed gPG Gdcajd CeGe GdOGFf cGaI GdGdJRGeGJ GdeJQJHI Ydi YbO GdcaGdI, eJi GeJfY eOjfg Yf SOGO GdOjf Gdecahd YfO Mdhd GdCLd MjK Enqf GdcaGdI Ve PeI Edi PeI ai GdeWGdHI HJfajP GdJRGe, hbO JSaQ GdcaGdI ai GdfgGjI Yf ZQe NGdU ddcajd(B. (3hEPG cGf GdCUd Cf CehGd GdeOjf JVef GdhaGA HOjhfg EdG Cf gPG GdeOjf bO jgOO HTHM GdEYSGQ , bO jJUQa ai Jdc GdCehGd JUQaG jfbU ef gPG GdVeGf HMjK dG Jcai GdCehGd ddhaGA HGdOjhf GdeJQJHI HPeJg ddOGFfjf(B.s
(3CWQhMI (B((3OcJhGQg(B)-(3LGeYI GdbGgQI, (B2022(3, bSe GdbGfhf GdeOfjs
(3HHdjhLQGajG(B: (3U(B. 329-342.s
Keywords: (3MeGjI Gdcajd aj eQMdJj eGbHd h eG HYO GHQGe YbO GdcaGdI s; (3GdQVG aj GdcaGdI s; (3JWHjb fXQjI GdSHH Ydi Yb GdcaGdI s; (3GKHGJ YbO GdcaGdI s; (3NUhUjI JaSjQ YbO GdcaGdI s; (3YOe GdJhSY aj JChjd QVG Gdcajd s; (3TQhW QLhY GdOGFf Ydi Gdcajds; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdeOfjs